2016
DOI: 10.1002/j.0022-0337.2016.80.1.tb06059.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Standardized Patients to Teach Interprofessional Competencies to Dental Students

Abstract: The aims of this study were to develop, implement, and evaluate a novel interprofessional standardized patient exercise (ISPE) with oral-systemic and interprofessional collaborative practice (IPCP) components. Dental students and doctor of nursing practice (DNP) students at one U.S. university participated in the simulation, which was primarily designed to test their teamwork skills. In spring 2014, DNP students worked in the dental clinics with dental students under the supervision of nursing and dental facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 24 publications
2
38
0
7
Order By: Relevance
“…The experiences of pre-registration student dentists, dental hygiene and therapy students and first-year dental nurses with regards to IPE in Portsmouth, found that all students had positive attitudes towards IPE and each of the three groups reported that IPE enhanced teamwork and development of professional relationships. 23 An IPE event involving dental students and student doctors of nursing practice 24 found that students were respectful of each needs. Within the UK, dental students and student dental technicians linked together in the provision of dentures for a patient, resulted in the majority of students recognizing the benefits of shared learning and valuing the roles of team members, the acquisition of teamwork skills for their future careers and ultimately improving patient care 25 .…”
Section: Effectiveness Of Interprofessional Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiences of pre-registration student dentists, dental hygiene and therapy students and first-year dental nurses with regards to IPE in Portsmouth, found that all students had positive attitudes towards IPE and each of the three groups reported that IPE enhanced teamwork and development of professional relationships. 23 An IPE event involving dental students and student doctors of nursing practice 24 found that students were respectful of each needs. Within the UK, dental students and student dental technicians linked together in the provision of dentures for a patient, resulted in the majority of students recognizing the benefits of shared learning and valuing the roles of team members, the acquisition of teamwork skills for their future careers and ultimately improving patient care 25 .…”
Section: Effectiveness Of Interprofessional Educationmentioning
confidence: 99%
“…It has been identified that working with simulated patients provided a powerful learning experience 14 . In an example of IPE involving dental students and student doctors of nursing practice, simulated patients with chronic medical diagnosis and orofacial symptoms promoted effective IPC 24 .…”
Section: Learning Activities and Learning Theoriesmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] The development of an SP encounter is a thorough and rigorous process, which often takes several weeks of planning and training before implementation. [20][21][22][23][24] Through SP encounters, students are able to develop confidence, 13,[25][26][27] improve clinical reasoning, 13,17 collaborate 14 and communicate interprofessionally, 28 and positively impact learner motivation 27,29 and clinical skill acquisition. 13,27,29,30 Standardized patient encounters also provide each of these learning outcomes in an a safe environment resembling clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…By teaching medical ethics to students of different health professional programs in an interdisciplinary and integrative setting, educators can inspire an atmosphere of cooperation and willingness to improve collaboration and communication, mutual respect and shared planning, and decision making in clinical practice [12]. Interprofessional collaboration is an ideal method to explore ethical dilemmas because it allows inclusion for all relevant professional perspectives and encourages collaboration and respect, while also highlighting the strengths of each individual profession's perspective towards patient care [13][14][15].…”
Section: Introductionmentioning
confidence: 99%